The selection of maxillary anterior teeth width in relation to facial measurements at different types of face form - Nagham H Kassab (University of Mosul, College of Dentistry, 2005)
Abstract It is difficult to determine the dimensions of maxillary anterior teeth for edentulous patient when pre-extraction records are not available. Therefore, the present clinical study was carried out to evaluate the relationships between maxillary anterior teeth measurements [canine arc distance (CARCD), central incisor width] and certain horizontal facial parameters which included: [(interzygomatic, inner and outer canthus and inter-pupillary) distances in addition to that (interalar, mouth and philtrum of upper lip) widths], and also to determine those relations at different types of facial form in both sexes for the best selection of maxillary anterior teeth widths. The facial and dental measurements were obtained directly from 100 Iraqi undergraduate dental students by using an electronic digital vernier caliper. Depending on facial index for each subject, the larger percentage of students (80%) had a leptoprosopic (long and narrow) face in which their facial indices were 90 or above, whereas 4% of students had a euryprosopic (square) face in which their facial indices 82.1-83.1; while 16% of those students had a mesoprosopic (ovoid) face in which their facial indices 85.3-89.5. The Pearson Product Moment Correlation Coefficient was used for all relationships and the results revealed that there was a significant correlation between CARCD and mouth width in males with leptoprosopic face while in those with mesoprosopic face the CARCD was significantly correlated with both mouth and interzygomatic widths but with higher correlation coefficient value being with mouth width, the maxillary central incisor width was significantly correlated with both inner canthal distance and philtrum width of upper lip but with higher correlation coefficient value being with first one. In females with leptoprosopic face, the CARCD had a high significant correlation coefficient with inner canthal distance; while in those with mesoprosopic face the maxillary central incisor width was significantly correlated with interzygomatic distance while the other correlations in different types of face form for both sexes were found to be in low magnitude and were notsignificant. On the above mentioned results, this study demonstrated that certain horizontal facial parameters could be used as a guide in maxillary anterior denture teeth selection to achieve the best esthetic result in each type of face form in both sexes